Responsibility of the Executive Authority for the Final Accounts under the Decision of the Federal Supreme Court No. 190/Federal/2023 - A. p Kawther Basim Al tameme (The college of law and political science journal, 2025)
The purpose of discussing the draft final account by the House of Representatives for the purpose of approving it is to verify the implementation of the general budget and that spending units do not go beyond the limits set for them, and to reveal deviations in implementation and prevent extravagance and waste in order to preserve public money. Therefore, the importance of the final account is no less than the importance of the general budget. Therefore, its failure to be prepared by the executive authority or approved by the legislative authority has an impact on public money, as the House of Representatives is responsible for monitoring all spending operations, and it is not permissible for it to neglect studying the draft final account and lose its intended purpose. At the time when the Council of Ministers did not adhere to the specified dates by which it should submit the draft final account, the House of Representatives also did not realize the importance of discussing and approving it, so it was negligent in the delay of the Council of Ministers in submitting it, and did not raise its political responsibility.